"Deter o día cunha flor" (2009), an excellent verse book of Luz Pozo Garza - López, Aurora; Pociña, Andrés (Madrygal. Revista de Estudios Gallegos, 2013)
This is a presentation and commentary of Deter o día cunha flor, at the moment the last verse book of Luz Pozo Garza; it will appear in the next book Á procura da poesía. Vida e obra de Luz Pozo Garza by Aurora López e Andrés Pociña, to be edited proximately.
Keywords: Luz Pozo Garza; Poems; Deter o día cunha flor